Development of A Montessori Book to Improve the Early Reading Skills for Elementary School Students - Dessy Dwitalia Sari; Tika Puspita Widya Rini (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to (1) produce Montessori reading books and (2) reveal the effectiveness of Montessori reading books in learning to improve the reading skills of first-grade elementary school students. This research is research and development (RnD). The research subjects were students and teachers of grade 1 elementary school. Data was obtained through interviews and observation. The products developed are validated by experts, and initial reading skills are carried out to obtain the effectiveness of the book. Product effectiveness is tested through quasi-experiments. Data analysis techniques used an independent sample t-test with a significant level of 0.05. The results of this study are in the form of Montessori reading books. (1) The results of the expert validation assessment show that the books developed are appropriate according to material experts in the "very good" category, media experts in the "good" category, and linguists in the "very good" category. Teacher and student responses to Montessori books in learning are categorized as "very good". (2). The results of the effectiveness test indicated that the book was effective in improving beginning reading skills. Based on the results of operational field trials, the value of p 0.05 means that there is a significant difference in students who carry out the learning process using Montessori books.